PENGARUH PEMBERIAN HORMON TIROKSIN (T4) DENGAN PERENDAMAN TERHADAP PERTUMBUHAN DAN TINGKAT KELULUSHIDUPAN BENIH IKAN GURAMI (Osphronemus gouramy Lac) - Oki Kurniawan; T Iskandar Johan; Jarod Setiaji (UIR Press, 2014)
The objective of this research was to examine the effect of giving tyroxin hormone (T4) with soaking on growth and survival of gouramy seed (O. gouramy Lac). The research was conducted at the Hatchery Faculty of Agriculture Riau Islamic University Pekanbaru from October to November 2009. Method used was experiment. Treatment consisted of P1 (without tyroxin hormone), P2 (0.3 mg/3 l water), P3 (0.9 mg/3 l water) and P4 (1.5 mg/3 l water). The resuts showed that the highest absolute growth weight was found on P4 of about 1.11 g, the highest absolute growth lenght on P4 of about 0.93 cm, and the highest daily speed growth on P4 of about 2.9%. The survival rate was found to be 100% for the whole treatments. The variation analysis was obtained that the use of tyroxin hormone with different dosages had no significant effect on growth rate of weight and lenght for gouramy seed.